Biopolymer-based functional films for packaging applications: A review - Abdullah,; Cai, Jiyang; Hafeez, Muhammad Adnan; Wang, Qun; Farooq, Shahzad; Huang, Qingrong; Tian, Wenni; Xiao, Jie (Frontiers in Nutrition, 2022)
Food packaging is a coordinated system comprising food processing, protection from contamination and adulteration, transportation and storage, and distribution and consumption at optimal cost with a minimum environmental impact to the packed food commodity. Active packaging involves deliberate addition of the functional ingredients either in the film or the package headspace to preserve the food quality, improve safety and nutrition aspects, and enhance the shelf-life. In this review, recent advances in the fabrication of biopolymer-based films, their classification (biodegradable-, active-, and intelligent packaging films), advanced fabrication strategies (composite-, multilayer-, and emulsified films), and special functions induced by the biopolymers to the film matrix (mechanical-, water resistance and gas barrier-, and optical properties, and bioactive compounds reservoir) were discussed. A summary of conclusions and future perspectives of biopolymer-based packaging films as advanced biomaterial in preserving the food quality, improving safety and nutrition aspects, and enhancing shelf-life of the products was proposed.